The Psychological Impact of Participation in Victim-Offender Mediation on Offenders: Evidence for Increased Compunction and Victim Empathy - Jonas, Jiska; Zebel, Sven; Claessen, Jacques; Nelen, Hans (Frontiers in Psychology, 2022)
Participation in victim-offender mediation (VOM) can reduce the risk of reoffending. However, relatively little is known about how VOM affects the intermediate psychological changes underlying this effect. It was hypothesized that VOM increases feelings of responsibility, guilt, and shame among offenders as well as empathy toward the victim. It was also expected that VOM leads to feelings of moral failure among offenders, increasing their intention to desist, and improving their relation with the victim, relatives, and community. Lastly, it was hypothesized that offenders may experience reduced rejection, concerns about condemnation, threat to their social moral identity, and victim blame following VOM. To this end, we compared psychological changes in offenders who participated in a VOM program in the Netherlands with those of offenders who were willing to but did not participate (total N = 86). A quasi-experimental, pre- and postmeasure research design was used to compare these groups. Our findings tentatively suggest that offenders who participate in VOM have more responsibility-taking and victim empathy, feel more guilt and shame, and experience higher moral failure than offenders who do not participate in VOM do. Offenders also reported feeling significantly less awkward about meeting the victim again after VOM. Future research should address how and to what degree these psychological changes translate into a lower risk of reoffending.